PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DENGAN MENGGUNAKAN PENDEKATAN PROBLEM POSING - Kurnia, Indri; Rosmaya, Rosmaya (LP4MK STKIP PGRI Lubuklinggau, 2023)
The purpose of the study was to determine how the problem posing approach in learning mathematics can improve mathematical critical thinking skills. This type of research is Quasi experimental with Post Test Only Control Group design. The population in this study were VIII grade students of SMP Negeri 12 Bandar Lampung. The cluster random sampling method was used to select sample members from the population without considering the students' ability level. The results showed that the problem posing approach with steps to create mathematical situations, formulate mathematical questions, solve mathematical problems, and apply mathematical concepts has a relationship with indicators of mathematical critical thinking skills. Indicators of critical thinking skills include interpretation, analysis, evaluation, inference, explanation, and self-regulation. So, it can be concluded, students' mathematical critical thinking skills can be improved using the problem posing approach.